2017
DOI: 10.1073/pnas.1614677114
|View full text |Cite
|
Sign up to set email alerts
|

Recovery sleep after extended wakefulness restores elevated A 1 adenosine receptor availability in the human brain

Abstract: Adenosine and functional A 1 adenosine receptor (A 1 AR) availability are supposed to mediate sleep-wake regulation and cognitive performance. We hypothesized that cerebral A 1 AR availability after an extended wake period decreases to a well-rested state after recovery sleep. [ 18 F]CPFPX positron emission tomography was used to quantify A 1 AR availability in 15 healthy male adults after 52 h of sleep deprivation and following 14 h of recovery sleep. Data were additionally compared with A 1 AR values after 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 60 publications
3
50
1
Order By: Relevance
“…Individual differences in caffeine sensitivity have been linked to genetic variations in the adenosine system (39,40). In a recent study using PET, we found that the degree of an individual's performance impairment after extended time awake was related to cerebral A 1 AR availability (29). Taken together, the adenosine system appears to be subject to individual variations that in turn contribute to the differences in the vulnerability to sleep loss.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Individual differences in caffeine sensitivity have been linked to genetic variations in the adenosine system (39,40). In a recent study using PET, we found that the degree of an individual's performance impairment after extended time awake was related to cerebral A 1 AR availability (29). Taken together, the adenosine system appears to be subject to individual variations that in turn contribute to the differences in the vulnerability to sleep loss.…”
Section: Discussionmentioning
confidence: 81%
“…The present study also reveals that acute ethanol administration is accompanied by a rapid increase in A 1 AR availability in the human brain and that the subjective sedating effects as assessed by the BAES correlate strongly with cerebral A 1 AR availability. Given the previously observed up-regulation of A 1 AR availability with extended time awake (28,29), the cerebral adenosine system might therefore represent a common pathway for both ethanol and sleep deprivation effects on performance. Behavioral studies have established a link between both stressors, providing evidence for additive or even synergistic detrimental effects on cognitive performance (30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 97%
“…The study design was described elsewhere (Elmenhorst et al ., ). In brief, participants came to the laboratory for one adaptation night and one baseline night (23:00–07:00 hours) before being sleep deprived for 58 h. Finally, participants had a 14‐h recovery night (17:00–07:00 hours).…”
Section: Methodsmentioning
confidence: 97%
“…Study procedures and neuropsychological tests were documented in detail in a previous publication (Elmenhorst et al, 2017). Study procedures and neuropsychological tests were documented in detail in a previous publication (Elmenhorst et al, 2017).…”
Section: Sd52 Studymentioning
confidence: 99%
“…In this study, we enrolled 14 young males (age: 28.21 ± 5.21 years, mean body mass index: 24.39 ± 3.58). Study procedures and neuropsychological tests were documented in detail in a previous publication (Elmenhorst et al, 2017). In brief, the participants were requested to maintain their regular sleep habits (time in bed: 23:00 hr to 7:00 hr), to refrain from caffeine and wear a wrist-actigraph during 1 week, 5 days, and 3 days before coming to the sleep research lab, respectively.…”
Section: Sd52 Studymentioning
confidence: 99%